Enterprise Architecture Design Using Togaf Framework In CV Widjojo - Valentinus, Nilo Legowo (International Journal of Advanced Science and Technology, 2020)
One important strategy in dealing with the development of information technology is the utilization and improvement of information systems support for the enterprise. This research was conducted at CV Widjojo. The governance of the implementation of information systems, the use of information technology and data management have not been maximized yet. A design is needed for the development of IT / IS governance in CV Widjojo. This study discusses how the process of developing Enterprise Architecture in CV Widjojo and how the analysis of the design results can be a reference for the development of IT / IS governance for the next few years. The method used in this research is TOGAF ADM. Preliminary phase analysis, vision architecture phase, business architecture phase, system information phase, technology architecture phase, opportunities and solution phase, and migration planning are carried out in describing the existing conditions and building the target architecture. The data in this study were obtained by conducting interviews, observation and study of literature. The results of this study in the form of a recommended enterprise architecture design, solutions to problems, and IT roadmap based on the analysis that has been done.